Melawan alienasi digital: Spiritualitas relasional sebagai antitesis phubbing dalam diskursus teologi komunikasi Kristen di era posdigital - Yusuf Slamet Handoko (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2025)
The post-digital era has given rise to the phenomenon of phubbing, with a prevalence of 49.3% among young people, creating a crisis of relational spirituality within Christian communities. This research aims to analyze phubbing as a manifestation of digital alienation from a Christian communication theology perspective and construct relational spirituality as its theological antithesis. Through literature study methods with an integrative theological reflection approach, this research explores the phenomenology of phubbing, the framework of relational spirituality, the construction of resistant communities, and the transformation of ministry. Findings indicate that phubbing represents a fundamental crisis in understanding the relational imago Dei, threatening fellowship that reflects Trinitarian love. Relational spirituality offers a comprehensive theological paradigm that integrates the wisdom of Christian tradition with contemporary digital realities. Practical implications include developing theological praxis for forming communities resistant to digital alienation and reconceptualizing pastoral ministry for the post-digital era, as well as creating compelling counter-narratives to digital culture's assumptions about connectivity as a substitute for authentic human development. Abstrak Era post-digital telah melahirkan fenomena phubbing dengan prevalensi 49,3% di kalangan generasi muda, menciptakan krisis spiritualitas relasional dalam komunitas Kristen. Penelitian ini bertujuan menganalisis phubbing sebagai manifestasi alienasi digital dalam perspektif teologi komunikasi Kristen dan mengkonstruksi spiritualitas relasional sebagai antitesis teologisnya. Melalui metode studi literatur dengan pendekatan teologis refleksi integratif, penelitian mengeksplorasi fenomenologi phubbing, kerangka spiritualitas relasional, konstruksi komunitas resisten, dan transformasi pelayanan. Temuan menunjukkan bahwa phubbing merepresentasikan krisis fundamental dalam pemahaman imago Dei yang relasional, mengancam persekutuan yang mencerminkan cinta Trinitas. Spiritualitas relasional menawarkan paradigma teologis komprehensif yang mengintegrasikan kebijaksanaan tradisi Kristen dengan realitas digital kontemporer. Implikasi praktisnya meliputi pengembangan praksis teologis untuk formasi komunitas yang resisten terhadap alienasi digital dan rekonseptualisasi pelayanan pastoral untuk era pasca-digital, menciptakan kontra-narasi terhadap asumsi kultur digital tentang konektivitas sebagai pengganti perkembangan manusia yang autentik.